(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article examines the impact of computer addiction on the emotional development of adolescents, identifies the main factors contributing to addiction, and explores methods of prevention and intervention, including the roles of parents, educators, and social support systems. The findings indicate that ensuring stability during adolescence requires fostering interests, identifying individual abilities, satisfying communication needs, and developing stress resilience. Special attention is given to effective time management, distinguishing between virtual and real environments, and promoting balanced adolescent development. Additionally, strategies for building psychological immunity against harmful computer games, online gambling, and excessive exposure to information streams are discussed.